Global Burden and Changing Trend of Hepatitis C Virus Infection in HIV-Positive and HIV-Negative MSM: A Systematic Review and Meta-Analysis - Zheng, Yang; Ying, Meike; Zhou, Yuqing; Lin, Yushi; Ren, Jingjing; Wu, Jie (Frontiers in Medicine, 2021)
Background: The disease burden of hepatitis C virus (HCV) infection in HIV-positive and HIV-negative men who have sex with men (MSM) is changing. We aim to provide an updated comprehensive estimate of HCV prevalence and incidence among the HIV-positive and HIV-negative MSM population at the country, regional, and global levels and their changing trends over time. Methods: PubMed, Embase, PsycINFO, CINAHL, and conference databases were searched and eligible records on the prevalence and incidence of HCV antibodies were selected and pooled via a random-effects model. Meta-regression was performed to demonstrate the association between the pooled rates and study year. Results: A total of 230 articles reporting 245 records from 51 countries with 445,883 participants and 704,249 follow-up person-years were included. The pooled prevalence of HCV in MSM was 5.9% (95% CI: 5.1–6.8), with substantial differences between countries and regions. Low- and lower-middle-income countries (12.3 and 7.0%) manifested a larger disease burden than high- and upper-middle-income countries (5.8 and 3.8%). HCV prevalence in HIV-positive MSM was substantially higher than in HIV-negative MSM (8.1 vs. 2.8%, p < 0.001). The pooled incidence of HCV was 8.6 (95% CI: 7.2–10.0) per 1,000 person-years, with an increasing trend over time, according to meta-regression (p < 0.05). Conclusion: Global HCV prevalence in MSM varies by region and HIV status. Behavior counseling and regular HCV monitoring are needed in HIV-positive subgroups and high-risk regions. Given the upward trend of HCV incidence and sexual risk behaviors, there is also a continued need to reinforce risk-reduction intervention. Systematic Review Registration: PROSPERO, identifier CRD42020211028; https://www.crd.york.ac.uk/prospero/.